PENGARUH PIJAT BAYI TERHADAP KENAIKAN BERAT BADAN BAYI PADA BAYI DENGAN BERAT BADAN LAHIR RENDAH (BBLR) DI RUANG BAYI RUMAH SAKIT BHAYANGKARA BANJARMASIN - Miranda Nur Aulia Resiani; Maolinda, Winda; Noor Hasanah, Siti (LPPM Universitas Sari Mulia, 2025)
Background: The World Health Organization (WHO) defines Low Birth Weight (LBW) as a birth weight of less than 2500 grams, regardless of gestational age. Data from newborns at Bhayangkara Hospital Banjarmasin between 2020 and 2023 show an annual increase in LBW cases, rising from 6.4% in 2020 to 13.7% in 2023. Massage therapy offers the advantage of being cost-effective. Moreover, complementary therapies are not only economical but also free from serious side effects, drug reactions, and are easy to administer and well-accepted by patients. Objective: To evaluate the effect of infant massage on weight gain in Low Birth Weight (LBW) infants in the infant ward of Bhayangkara Hospital Banjarmasin. Methods: This study employed a quasi-experimental design, which is a basic unit of experimental research and does not utilise randomised control or comparison groups. The sample consisted of 15 infants. A one-group pretest-posttest design with paired T-test analysis was implemented. Results: The study found a significant difference in infant weight before and after seven consecutive days of massage. Among the 15 infant samples, the average weight increased from 2390 grams to 2553 grams. The paired T-test results between the pretest and posttest groups revealed a p-value of 0.001 (p < 0.05), indicating a significant increase in weight after infant massage. Conclusion: Infant massage has a significant effect on increasing weight in LBW infants. Keywords: LBW, Weight Gain, Infant Massage